Pengaruh Pendekatan Konstruktivisme Berbasis Learning Cycle 5E Terhadap Hasil Belajar Siswa Kelas Xi Pada Materi Larutan Penyangga Di Sma Kristen Kotamobagu - Fina Hamise; I Dewe Ketut Anom; Jeanne Tuerah (Chemistry Department, Universitas Negeri Manado, 2019)
This study aims to determine the effect of using the constructivist approach based on the 5E learning cycle on the learning outcomes of class XI students on buffer solutions. This research was conducted in classes XI IPA 1 and XI IPA 2 of Kotamobagu Christian High School. The method used is an experimental method with a post – test only control design. The research sample consisted of 23 randomly selected students. The experimental class uses the 5E learning cycle model, the control class uses conventional learning. Student learning outcomes data obtained from post-test scores. The analysis of research data shows that there are differences in student learning outcomes, which are taught using the 5E learning cycle model and those using conventional learning. The data analysis used the t-test with a significance level of α = 0.05. Statistical analysis of student learning outcomes obtained tcount> ttable or 4.90> 1.68. So it can be concluded that there are differences between student learning outcomes using the constructivism approach based on the 5E learning cycle and student learning outcomes using conventional learning.